Thermal compensation system in advanced and third generation gravitational wave interferometric detectors. (May 2019) - Aiello, L; Cesarini, E; Fafone, V; Lorenzini, M; Minenkov, Y; Nardecchia, I; Rocchi, A; Sequino, V
Abstract: On September 14 th 2015 the first gravitational wave signal has been detected by the Advanced LIGO interferometers, opening the era of the gravitational astronomy and giving new opportunities to investigate the universe. The Advanced LIGO and Advanced Virgo interferometers are now back in a commissioning phase in order to improve their sensitivity for the next observing run, which will start in the first months of 2019. In the high-frequencies region of their sensitivity band, the detectors are shot-noise limited: the sensitivity in this frequency window could be improved increasing the laser input power, but this increases also the optical aberrations due to the thermal effects. The optical power absorptions in the substrate and coatings of the optics induce both an increase of the optical path length in the substrates of the mirrors (thermal lensing) and a thermal expansion of the optic itself along the optical axis (thermo-elastic deformation). Both these aberrations reduce the sensitivity of the detector, limiting its performances. In order to face and minimize them, an adaptive Thermal Compensation System is required in order to guarantee the proper operation of the interferometer. An overview of the present Thermal Compensation System system installed on Advanced Virgo, with also a focus on the possible improvements of the actual actuators for the next generation of detectors, is presented here.